OPTIMIZATION OF OBSTETRICS AND GYNECOLOGY CLINIC SERVICE VISITS WITH A MARKETING PLAN APPROACH AND PUBLICATION ON SOCIAL MEDIA - Athallandi, Kemal; Hariyanti, Tita; Mardiana Kusumawati, Anita (Universitas Brawijaya, 2025)
Quality antenatal care examinations can detect the risk of pregnancy and childbirth so that they can play an essential role in reducing maternal mortality in Indonesia. However, obstetric and gynecology clinic patient visits are not always high. Even in a private hospital where this study was conducted, the clinic visit rate became one of the outpatient clinics with the lowest number of visits. The purpose of this study is to find out how to optimize obstetrics and gynecology clinic visits. This study uses a qualitative method with a case study approach. Data collection was carried out by in-depth interviews, observations, and document studies. After that, a fishbone analysis is carried out to find out the root of the problem. Alternative solutions to problems are identified through literature studies and brainstorming. The results of this study show that two themes cause the problem of non-optimal obstetric and gynecology service visits. The first theme is that there is no marketing plan yet. The subtheme of this problem is that there has never been an analysis of hospital data for marketing activities, and there has been no marketing planning. The second is the lack of optimal service publication on social media. The subtheme of this problem is due to the lack of planning in the publication of social media content, the lack of standard operational procedures related to the publication of content on social media, and the limitations of marketing teams in content creation ideas. The problem of suboptimal obstetric and gynecology service visits at private hospitals can be caused by the lack of marketing planning and suboptimal publication of obstetrics and gynecology clinic services on social media. The hospital marketing team can compile marketing plans and publish hospital service content on social media to increase the number of patient visits.